Agent-Based Modeling in Hierarchical Control of Swarms During Evacuation - Janovská, Kristýna; Surynek, Pavel (SN computer science, 2022)
We address the problem of evacuation from the perspective of agent-based modeling (ABM) in this paper. The evacuation problem is modeled as a navigation of multiple agents that spatially interact with each other in a known environment. The environment is divided into a danger and a safe zone while the task of agents is to move from the danger zone to the safe one in a collision-free manner. Unlike previous approaches that model the environment as a discrete graph with agents placed in its vertices, at most one agent per vertex, our approach adopts various continuous aspects such as a grid-based embedding of the environment into 2D space and continuous line of sight of agents. In addition to this, we adopt hierarchical structure of multi-agent system in which so called leading agents are more informed having full knowledge of other agents and are capable of performing multi-agent pathfinding (MAPF) via centralized algorithms like conflict-based search (CBS) while so called follower agents with limited knowledge about other agents are modeled using simple local rules. Our experimental evaluation indicates that suggested hierarchical modeling approach can serve as a tool for studying the progress and the efficiency of evacuation processes in different environments.